ANALISA METODE FORECASTING DALAM PENYUSUNAN ANGGARAN PENJUALAN DAN ANGGARAN PRODUKSI PADA RUMAH PRODUKSI DNA BAKERY DI KECAMATAN TAMBAN KABUPATEN BARITO KUALA - Mailiana Mailiana; Diana Hayati; Penta Lestarini Budiati; Saniah Saniah (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this study is to determine how to prepare a forecast and sales budget and production budget for DNA Bakery bread in 2024-2025 at the DNA Bakery Production House in Tamban District. The method used in this study is descriptive and quantitative. The results of the study stated that the sales forecast for DNA Bakery bread with several tofu flavors in 2024 was 7,560 and in 2025 it was 4,320, while 2-flavor tofu bread in 2024 was 3,920 pcs and in 2025 it was 4,200 pcs, and 3-flavor bread in 2024 was 3,770 pcs and in 2025 it was 4,040 pcs. The sales budget for DNA Bakery bread at the DNA Bakery Production House in Tamban District in 2024-2025 is IDR 107,150,000. The production budget for DNA Bakery bread at the DNA Bakery Production House in Tamban District in 2024 was 15,434 pcs and in 2025 it was 12,672 pcs.